Measurement of flow-mediated dilatation using a pulse oximeter probe (Comparison with RH-PAT) - Satoshi SHIMAWAKI; Miyu TAKITA; Yuri KIMURA (Nihon Kikai Gakkai ronbunshu, 2025)
Flow-dependent dilatation test using Endo-PAT is conventionally used to evaluate vascular endothelial function; however, this method is costly. Therefore, in the previous paper, the author presented an alternative method to Endo-PAT using vascular visualization technology. However, this device was impractical owing its large size. Therefore, we thought it possible to use a pulse oximeter probe similar in mechanism to the device shown in the previous paper. The purpose of this study was to determine whether vasodilatation following cuff pressure release in the upper arm can be detected using a pulse oximeter probe. We also determined the correlation between vasodilation measurement values and the reactive hyperemia index (RHI). Using a sample of 49 healthy subjects, we measured the amount of light transmitted through the fingertip using a pulse oximeter probe and recorded digital pulse volume by RH-PAT (Reactive hyperemia peripheral artery tonometry). The amount of light transmitted through the index finger tip was obtained by separately measuring the output voltage of a photodiode receiving light emitted from a red light-emitting diode (LED, wavelength: 660 nm) or an infrared LED (940 nm) incorporated within the pulse oximeter probe. During this process, the upper arm was compressed for 5 min with a cuff at 200 mmHg so that output voltages before and after cuff compression release could be obtained. We observed decreased output voltages for both lights following cuff pressure release, presumably caused by vasodilation. From the temporal variation in output voltage, R2 was defined as the ratio of the increase in output voltage after cuff compression to the decrease in output voltage following cuff compression release. We found significant positive correlations between RHI and R2 for both red and infrared light (ρ = 0.53 and 0.55). Next, when comparing RHI quartiles, the R2 value of the lowest RHI quartile was significantly smaller than those of higher RHI quartiles (p < 0.05). These results show that the pulse oximeter probe was able to detect vasodilation following cuff pressure release, and that this was significantly correlated with RHI values recorded via RH-PAT.